An Epidermal Stimulation and Sensing Platform for Sensorimotor Prosthetic Control, Management of Lower Back Exertion, and Electrical Muscle Activation. Issue 22 (15th October 2015) - Xu, Baoxing; Akhtar, Aadeel; Liu, Yuhao; Chen, Hang; Yeo, Woon‐Hong; Park, Sung II; Boyce, Brandon; Kim, Hyunjin; Yu, Jiwoo; Lai, Hsin‐Yen; Jung, Sungyoung; Zhou, Yuhao; et al.
Abstract : The design of an ultrathin, conformal electronic device that integrates electrotactile stimulation with electromyography, temperature, and strain sensing in a single, simple platform is reported. Experiments demonstrate simultaneous use of multiple modes of operation of this type of device in the sensorimotor control of robotic systems, in the monitoring of lower back exertion and in muscle stimulation.